Biodegradation of Tapis crude oil using consortium of bacteria and fungi: optimization of crude oil concentration and duration of incubation by Response Surface Methodology - Ainon Hamzah; Vidyah Manikan; Nur Ain Fathiha Abd Aziz (Penerbit Universiti Kebangsaan Malaysia IP, 2017)
Response surface analysis was conducted to optimize the concentrations of Tapis crude oil and duration of incubation in order to achieve optimal microbial growth and crude oil biodegradation. Central Composite Rotatable Design (CCRD) was employed, where the design contained 13 experimental runs with different combinations of incubation time and crude oil concentration. The cultures containing mineral salt medium (MSM) with varying crude oil concentrations were incubated at 30°C, pH6.5 with 150 rpm agitation for 120-336 h. The inoculum contained a consortium of previously identified as oil degrading bacteria and fungi, namely Pseudomonas aeruginosa UKMP-14T, Acinetobacter baumannii UKMP-12T and Trichoderma sp. UKMP-1M and UKMP-2M. The analysis showed the duration of incubation plays a significant role (p<0.05) in affecting the bacterial growth and percentage of total petroleum hydrocarbon (TPH) biodegradation, meanwhile concentrations of Tapis crude oil has insignificant effect on the responses. Interaction of the two variables was found to be significant in affecting all the three responses, namely bacterial population, fungal biomass and percentage of TPH biodegradation. It was predicted through the CCRD that the percentage of biodegradation can be optimized to reach 86% on the 270th h when 5% (v/v) crude oil was used. This predicted value was verified to be achievable and reproducible through validation experiments.